Recruiting older participants: evaluating the role of message framing in willingness to enroll in wearable robot experiments - Clio Yuen Man Cheng; Vivian W. Q. Lou (Cogent Social Sciences)
Willingness to enroll in experiments plays a vital role in user-centered design, particularly in emerging domains such as wearable robots for daily living assistance, where recruiting older adults poses challenges. Guided by the integration of prospect theory and the senior technology acceptance model, this study aims to investigate the persuasive effects of message framing, specifically the valence (gain: positive framing versus loss: negative framing), in the form of flyers on older adults’ willingness to participate in real-life wearable robot experiments. The survey data were collected from 176 online participants (Mage = 61.05; SD = 6.49). Multivariate analysis of variance indicates that gain-framed messages significantly influence perceived health benefits (F(1, 174) = 14.363, p < .001, ɳ2 = .09, 95% CI: .03-1.00). However, message frames do not directly impact the perceived effectiveness of flyers or willingness to enroll. Mediation analysis reveals that gain-framed messages enhance older adults’ willingness to enroll in wearable robot experiments through their perception of health benefits (IE: β = −.19, 95% CI: −.38– −.06, p = .017). This study contributes to the understanding of the persuasive effects of message framing on older adults’ willingness to enroll in wearable robot experiments, ultimately fostering advancements in the field and enhancing health outcomes and well-being for older adults.